Effect of runner dimensions on cavity filling in microinjection moulding for defect-free parts - Abdullahi, A.A.; Choudhury, I.A.; Azuddin, M. (Asian Research Publishing Network, 2016)
Modelling and simulation of injection moulding process is an important technique that could shorten production cycle time with improved productivity for defect-free parts. This technique is more suitable for micro-injection moulding (μIM) process as likely defects during production can be predicted. Therefore, this study aims to investigate the effect of runner dimensions on quality of moulded parts. Solidworks plastic simulation software was used for mould cavity filling analysis of ASTM D638-10 Type V. The dimensions of the runner and the injection point investigated are 0.5 mm, 0.8 mm, 1 mm and 2 mm. The moulded part quality characteristics predicted are filling time, sink mark and air trap. In addition, analytical model for prediction of melt pressure as a function of both melt filled distance (xo) and the temperature is developed. The theoretical model and simulation software are useful for investigations of defect-free parts in μIM process.